Intermediate Temperature Fuel Cell and Oxygen Reduction Studies With Carbon-Supported Platinum Alloy Catalysts in Phosphoric Acid Based Systems - Mamlouk, Mohamed; Jang, Jong Hyun; Scott, Keith (ASME, 2012)
The oxygen reduction activities of platinum and platinum alloy catalysts were evaluated at temperatures up to 150 degrees C in phosphoric acid solution. The oxygen reduction currents and open circuit potentials were measured using chronoamperometry with double potential steps to eliminate the effects of double layer charging currents and metal deactivationcould be eliminated effectively. Based on the mass activity at 0.7 V versus Ag/AgCl, the commercial PtNi catalyst showed higher performances than commercial Pt catalyst at 150 degrees C. The commercial PtCo catalyst showed high activities at 90 degrees C and 120 degrees C. Intermediate temperature fuel cells based on phosphoric acid doped polybenzimidazole membranes were tested with the alloy cathode catalysts. In the case of Pt-Fe alloy an enhanced performance was achieved in comparison to that with Pt carbon catalysts. DOI: 10.1115/1.4004461]
Keywords: POLYMER ELECTROLYTE MEMBRANE; PT-CO ALLOYS; DOPED POLYBENZIMIDAZOLE; MICROEMULSION METHOD; PARTICLE-SIZE; ELECTROCATALYSTS; PERFORMANCE; SURFACE; FE; NI